Estruturas de governança das escolas municipais de Castanhal, Pará - CASIMIRO, Aline Marques (Universidade Federal do Pará, 2018)
In this master dissertation, governance is debated as a result of structures that are formed by the interaction among actors who work in public scholar organizations, with focus in schools in the municipality of Castanhal. The majority of theses schools have not reached the goals of the IDEB projected to the final series of elementary schools. It is considered that structures that generate governance offer the conditions to the acting of management that serve to an educational policy. Thus, to understand the relationship between governance and the results related to the performance of the learning community, the starting point is the identification of the governance structures of the public schools of Castanhal. It has as a methodologic classification the qualitative approach and a descriptive objetive. The assumed procedures to data collection were bibliographic and documental and case study. It was used the semi structured interview thecnic applied to municipal secretary of education; of questionaries applied to managers of the selected schools. It is inferred from the research results that hierarchical structures, the ones which offer few conditions to the participation of interested actors, do not contribute to school performances of the students regarding the measured variables by IDEB. The organizations that privilege the power sharing are in front of those of centralized structure, however, they still need to dispose of monitoring instruments of the actor’s performance and of made decisions. The visualization of the way as the governance structures are disposed, the structures of governance of the schools of the municipality of Castanhal demonstrate that, while contemplating the elements here proposed, they may help in the identification of obstacles to the achievement of the goals related to the teaching-learning process.